Learning, Decisions and Transformation in Critical Care Nursing Practice - Hough, M Catherine (Nursing ethics, 2008)
Critical care nurses are key providers in a high acuity environment. This qualitative research study explored ethical decision making in a critical care practice setting. Fifteen critical care nurses with varying experience and education levels were purposively sampled to assure the representativeness of the data. The theoretical concepts of experiential learning, perspective transformation, reflection-in-action and principle-based ethics were used as a framework for eliciting information from the participants. A new model of focused reflection in ethical decision making was developed. Findings showed that having a role model or mentor to help guide the ethical decision-making process was critical for focused ethical discourse and the decision making.